2007
DOI: 10.1074/jbc.m702753200
|View full text |Cite
|
Sign up to set email alerts
|

Repression by Binding of H-NS within the Transcription Unit

Abstract: H-NS inhibits transcription by forming repressing nucleoprotein complexes next to promoters. We investigated repression by binding of H-NS within the transcription unit using the bgl and proU operons. Repression of both operons requires a downstream regulatory element (DRE) in addition to an upstream element (URE). In bgl, H-NS binds to a region located between 600 to 700 bp downstream of the transcription start site, whereas in proU the DRE extends up to position ؉270. We show that binding of H-NS to the bgl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 66 publications
2
75
0
Order By: Relevance
“…Both the proU and bgl operons have upstream regulatory elements (UREs) and DREs that are essential for H-NS repression (20). It has been demonstrated that binding of H-NS at the bgl DRE inhibits transcription initiation at a step prior to open complex formation (20) in a manner similar to that previously described for H-NS repression via the proU DRE (13). It is unclear whether H-NS repression via a DRE is a consequence of RNA polymerase (RNAP) being trapped in a closed complex or whether RNAP is excluded (20).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Both the proU and bgl operons have upstream regulatory elements (UREs) and DREs that are essential for H-NS repression (20). It has been demonstrated that binding of H-NS at the bgl DRE inhibits transcription initiation at a step prior to open complex formation (20) in a manner similar to that previously described for H-NS repression via the proU DRE (13). It is unclear whether H-NS repression via a DRE is a consequence of RNA polymerase (RNAP) being trapped in a closed complex or whether RNAP is excluded (20).…”
Section: Discussionmentioning
confidence: 61%
“…It has been demonstrated that binding of H-NS at the bgl DRE inhibits transcription initiation at a step prior to open complex formation (20) in a manner similar to that previously described for H-NS repression via the proU DRE (13). It is unclear whether H-NS repression via a DRE is a consequence of RNA polymerase (RNAP) being trapped in a closed complex or whether RNAP is excluded (20). A number of models have been proposed for the repression of transcription by H-NS via a DRE.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In particular, hns transcription is down-regulated, and H-NS activity was shown to be diminished (Fig. 3); H-NS activity is diminished at high osmolarity (51). Two of the genes that are repressed by H-NS and induced by high osmolarity, bolA and osmC, are also upregulated in the microarray comparison (Figs.…”
Section: Loss Of Cydb Causes Diminished Respirationmentioning
confidence: 89%